Dual-channel oxygen supply floating cathode electro-Fenton system and preparation method and application thereof

By loading phenolic resin and hydrophobic organic polymer on carbonized wood, a floating cathode with an ordered pore structure was solved, and the problems of low oxygen mass transfer efficiency and poor electrode stability in traditional electrofenton reaction were achieved, and efficient H2O2 generation and Stable operation.

CN119191481AActive Publication Date: 2024-12-27SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411181285.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-27
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

Under natural conditions, the traditional electrofenton reaction system has low H2O2 generation efficiency due to the low concentration of dissolved oxygen in the aqueous phase, and the gas diffusion electrode is prone to overflow and uneven current distribution after long-term operation, which limits its size. Scale application.

Method used

Carbonized wood with ordered vertical channels is used as the floating cathode and phenolic resin and hydrophobic organic polymer are loaded thereon to construct a lateral reaction system to improve oxygen mass transfer efficiency and H2O2 generation efficiency and reduce side reaction losses.

Benefits of technology

It realizes efficient H2O2 production without aeration, improves the stability and yield of electrofenton reaction, and is suitable for large-scale wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191481A_ABST
    Figure CN119191481A_ABST
Patent Text Reader

Abstract

The invention discloses a dual-channel oxygen supply floating cathode electro-Fenton system and a preparation method and application thereof. The floating cathode electro-Fenton system comprises a floating cathode and an anode, wherein the floating cathode and the anode form a transverse reaction system; the floating cathode comprises carbonized wood with orderly arranged vertical pore channels, and phenolic resin and a hydrophobic organic polymer which are loaded in the carbonized wood. In the floating cathode electro-Fenton system, a floating cathode and an anode form a transverse reactor together. Due to the design, oxygen generated by the anode and oxygen in air can be better and directionally transmitted through the vertical channels which are orderly arranged in the floating cathode. Therefore, the floating cathode can utilize the upper and lower oxygen at the same time. Besides, due to the structure, generated H2O2 can be diffused out of the electrode in time, loss caused by side reaction is reduced, and therefore the efficient electro-Fenton device without aeration is constructed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrocatalysis technology, and in particular to a dual-channel oxygen supply floating cathode electro-Fenton system and a preparation method and application thereof. Background Art

[0002] As antibiotics become more widely distributed in the natural environment, the difficulty of antibiotic degradation in the environment has also increased. This has led to the massive introduction of persistent antibiotic genes in pathogens, which in turn has made the development of efficient antibiotic removal technologies in water a top priority. In the past few decades, various advanced oxidation process technologies have been developed to remove organic pollutants from wastewater. In particular, the Fenton reaction process, which produces hydroxyl radicals through solution chemistry or electrochemistry, has attracted widespread attention. Compared with the traditional solution chemistry Fenton reaction, the electro-Fenton process has the advantage of in-situ generation and activation of H2O2, and is therefore considered to be a safe, green and efficient process.

[0003] In the electro-Fenton system, the key factors to be considered for achieving an efficient H2O2 production process include catalyst selectivity, oxygen mass transfer, and electron transfer at the cathode reaction interface. To this end, many electrocatalysts with high reduction selectivity have been widely developed and applied, such as carbon black, carbon cloth, graphite felt and other carbon-based materials. These materials are highly favored due to their excellent conductivity, large specific surface area, good selectivity and affordable price. However, under natural conditions, the dissolved oxygen concentration in the water phase is low (only 1×10 -3 mol·dm -3 ), so the reaction is limited by low oxygen mass transfer, and it is difficult to effectively increase the H2O2 concentration. The traditional electro-Fenton reaction system requires an additional aeration device to ensure that the cathode part has sufficient oxygen supply to maintain the reaction. However, this leads to huge energy consumption, limiting the large-scale application prospects of the system. In this case, it becomes very important to design an efficient oxygen supply catalytic cathode and a suitable reactor.

[0004] The gas diffusion electrode is the most widely used method. The electrode consists of a catalyst layer, a current collecting layer and a gas diffusion layer. Through the gas diffusion layer, oxygen can be directly supplied from the outside to the catalyst layer without dissolving in the electrolyte. -3 mol·dm -3 ) is much higher than that in the water phase, so this innovative design overcomes the limitation of low dissolved oxygen concentration, thereby effectively improving the electrosynthesis efficiency of H2O2. Over the years, many researchers have been working on improving the catalytic layer of gas diffusion electrodes to increase the production of hydrogen peroxide, but relatively little research has been done on the gas diffusion layer.

[0005] During the reaction, the gas diffusion layer is crucial to maintaining the three-phase reaction interface of oxygen, catalyst and electrolyte. However, the disordered and tortuous diffusion channels within the layer hinder the effective transfer of gas and liquid, affecting the reaction kinetics, and making it difficult for the generated products to diffuse out of the reaction interface, causing side reactions and decomposing H2O2. In addition, since gas diffusion electrodes are mostly used in vertical reactors, water overflow will occur after a long period of reaction, so the electrode cannot operate stably for a long time. At the same time, the different water pressures it is subjected to in the vertical state will lead to uneven current distribution, which in turn affects the cathode performance, which is not conducive to the application of the electrode in large-scale sewage treatment. Summary of the invention

[0006] The purpose of the present invention is to achieve effective oxygen mass transfer and promote efficient production of H2O2 by optimizing the transmission channel structure inside the electrode in a floating cathode electro-Fenton system.

[0007] A first aspect of the present invention is:

[0008] A floating cathode electro-Fenton system is provided.

[0009] A second aspect of the present invention is:

[0010] Provided is a method for preparing a floating cathode electro-Fenton system.

[0011] The third aspect of the present invention is:

[0012] Application of the floating cathode electro-Fenton system.

[0013] Specifically, the technical solution adopted according to the first aspect of the present invention is:

[0014] A floating cathode electro-Fenton system, comprising a floating cathode and an anode forming a lateral reaction system with the floating cathode;

[0015] The floating cathode includes carbonized wood with orderly arranged vertical pores, and phenolic resin and hydrophobic organic polymer loaded in the carbonized wood.

[0016] According to the embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects:

[0017] The floating cathode electro-Fenton system of the present invention uses carbonized wood loaded with phenolic resin and hydrophobic organic polymer as a floating cathode, wherein the phenolic resin is used as an active substance to provide active sites. In order to increase the yield of H2O2, the hydrophobic organic polymer is introduced into the floating cathode to give it hydrophobic properties. Since the 2e-ORR reaction is a three-phase reaction, the electrode has a certain hydrophobicity, which is conducive to forming a three-phase reaction interface.

[0018] The floating cathode electro-Fenton system of the present invention uses the orderly arranged vertical channels in the wood substrate as transmission channels, so that substances can be transmitted directionally in the channels without obstacles. This structure can not only better utilize the oxygen above and below at the same time, but also make the generated H2O2 diffuse out of the electrode in time, reducing the loss caused by side reactions, thereby constructing a high-efficiency electro-Fenton device that does not require aeration.

[0019] In the floating cathode electro-Fenton system of the present invention, the floating cathode and the anode together constitute a lateral reactor. This design enables the oxygen generated by the anode and the oxygen in the air to be better transmitted in a directional manner through the vertical channels arranged in an orderly manner inside the floating cathode. Therefore, the floating cathode can simultaneously utilize the oxygen above and below, thereby achieving a high yield of H2O2. In addition, this structure enables the generated H2O2 to diffuse out of the electrode in a timely manner, reducing the loss caused by side reactions, thereby constructing an efficient electro-Fenton device that does not require aeration.

[0020] According to one embodiment of the present invention, the floating cathode floats above the solution to be treated, and the anode is placed below the solution to be treated to form a horizontal reactor, so that the oxygen generated by the anode below can be more smoothly delivered to the cathode above. Finally, the cathode above can more smoothly utilize the oxygen below and the oxygen in the air above.

[0021] According to one embodiment of the present invention, the mass ratio of the phenolic resin and the hydrophobic organic polymer loaded in the carbonized wood is 16-110:391-780.

[0022] According to one embodiment of the present invention, the mass ratio of the phenolic resin and the hydrophobic organic polymer loaded in the carbonized wood is 41-110:391-780.

[0023] According to one embodiment of the present invention, the mass ratio of the phenolic resin and the hydrophobic organic polymer loaded in the carbonized wood is 16-110:524-780.

[0024] The amount of hydrophobic organic polymer loaded in the carbonized wood determines the hydrophobicity of the floating cathode. Although the hydrophobic design can enhance the diffusion of O2 and achieve a rich three-phase interface, thereby synergistically improving the performance, the excessive use of hydrophobic organic polymer coating may hinder the transport of e-, thereby offsetting its potential advantages. Therefore, finding the optimal hydrophobic organic polymer loading is of vital importance for optimizing the electrocatalytic efficiency.

[0025] The amount of phenolic resin loaded in the carbonized wood affects the reactivity of the floating cathode.

[0026] According to one embodiment of the present invention, the hydrophobic organic polymer includes polytetrafluoroethylene.

[0027] According to one embodiment of the present invention, the carbonized wood includes carbonized pine wood.

[0028] According to one embodiment of the present invention, the thickness of the carbonized wood is 2-6 mm.

[0029] According to one embodiment of the present invention, the thickness of the carbonized wood is 2-4 mm.

[0030] According to one embodiment of the present invention, the thickness of the carbonized wood is 4-6 mm.

[0031] According to one embodiment of the present invention, in the floating cathode electro-Fenton system, a metal oxide electrode is used as a counter electrode.

[0032] Specifically, the technical solution adopted according to the second aspect of the present invention is:

[0033] A method for preparing the floating cathode electro-Fenton system comprises the following steps:

[0034] After carbonizing the wood, it is immersed in a phenolic resin precursor solution. After a hydrothermal reaction, the phenolic resin is in situ formed in the pores of the wood to obtain RF-CW.

[0035] The RF-CW is immersed in a hydrophobic organic polymer solution, taken out, dried, and then heat-treated to obtain a floating cathode;

[0036] The floating cathode is coupled to the anode to form a lateral reaction system to obtain the floating cathode electro-Fenton system.

[0037] According to the embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects:

[0038] The present invention carbonizes the wood to construct natural orderly arranged wood pores, and through a hydrothermal reaction, the phenolic resin can be evenly distributed inside the wood pores without destroying the wood pore structure.

[0039] It should be noted that if the phenolic resin is loaded into the carbonized pine wood directly by impregnation with phenolic resin instead of using the in-situ hydrothermal method, since phenolic resin is insoluble in water, stirring is often required. After stirring, the pore structure inside the wood will be destroyed, making it difficult for the phenolic resin to be evenly distributed inside the pores.

[0040] According to one embodiment of the present invention, the carbonizing of wood further comprises the following steps: cutting the wood into wood chips perpendicular to its growth direction, placing the wood chips in a protective atmosphere, and heating the chips at 800-850° C. to obtain carbonized wood having orderly arranged vertical pores.

[0041] Under high temperature, the organic matter in the wood gradually decomposes and volatilizes, leaving carbonaceous residues. In the presence of a pore structure, this process will cause the wood around the pore to be filled and wrapped by the residues. However, since the pores are arranged vertically, the carbonized residues will fill and form along the direction of the pores, making the final carbonized pine wood have an orderly vertical pore structure.

[0042] According to one embodiment of the present invention, the carbonization time of the wood is 6-6.5 hours.

[0043] According to one embodiment of the present invention, the raw material of the carbonized wood is pine wood. During the growth process, pine wood itself forms a channel structure perpendicular to the axis of the trunk for transporting water and nutrients. After the pine wood is cut into thin slices perpendicular to its growth direction, these channels still remain perpendicular to the surface of the sheet. Through long-term heat treatment at high temperature (800-850°C) and in a protective atmosphere, the organic matter in the wood is decomposed and volatilized, leaving carbonaceous residues to fill the channels. Since the channels are arranged vertically, the carbonized residues are filled and formed along the direction of the channels, eventually forming a carbonized pine wood material with an orderly arranged vertical channel structure.

[0044] According to one embodiment of the present invention, the raw materials of the phenolic resin precursor solution include the following components: resorcinol, formaldehyde and ammonia water.

[0045] According to one embodiment of the present invention, during the hydrothermal reaction, the temperature is maintained at 250-260°C.

[0046] According to one embodiment of the present invention, the hydrothermal reaction time is 24-26 hours.

[0047] According to one embodiment of the present invention, the temperature of the heat treatment is 300-310°C.

[0048] According to one embodiment of the present invention, the heat treatment has a treatment time of 2-2.5 hours.

[0049] Another aspect of the present invention provides a method for degrading tetracycline in a solution using a floating cathode electro-Fenton system, comprising the following steps:

[0050] A solution containing tetracycline and a catalyst are added to the floating cathode electro-Fenton system to obtain a mixed solution, which is electrolyzed to degrade the tetracycline in the solution.

[0051] According to one embodiment of the present invention, the catalyst comprises Fe 2+ Compounds, of which Fe 2+ The concentration in the mixed solution is 0.2-0.4 mol / L.

[0052] According to one embodiment of the present invention, the pH value of the mixed solution is 1-5.

[0053] According to one embodiment of the present invention, the pH value of the mixed solution is 1-3.

[0054] According to one embodiment of the present invention, the pH value of the mixed solution is 3-5.

[0055] According to one embodiment of the present invention, during the electrolysis process, the current density is 10-20 mA·cm -2 .

[0056] According to one embodiment of the present invention, during the electrolysis process, the current density is 10-15 mA·cm -2 .

[0057] According to one embodiment of the present invention, during the electrolysis process, the current density is 15-20 mA·cm -2 .

[0058] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0060] Figure 1 Schematic diagram of the floating cathode electro-Fenton system in Example 1.

[0061] Figure 2 Schematic diagram of the cathode preparation process in Example 1.

[0062] Figure 3 This is a test chart of H2O2 yield of Examples 1-3.

[0063] Figure 4 It is the H2O2 yield test graph of Example 1 and Example 4-5.

[0064] Figure 5 It is the H2O2 yield test graph of Example 1 and Examples 6-7.

[0065] Figure 6 The contact angle test diagrams of Example 1 and Examples 6-7 are shown.

[0066] Figure 7 It is a test graph of H2O2 yield of Example 1 and Examples 10-11.

[0067] Figure 8 This is a test chart of H2O2 yield of Example 1 and Examples 12-13.

[0068] Fig. 9 This is a test graph of H2O2 yield of Example 1 and Examples 14-15.

[0069] Fig.10 This is a test chart of H2O2 yield of Example 1, Example 16 and Comparative Example 4.

[0070] Fig.11 It is a test chart of H2O2 yield of Example 1 and Comparative Examples 1-3.

[0071] Fig.12 This is the SEM image of the P / RF-CW prepared in Example 1.

[0072] Fig.13 This is the SEM image of P / RF-CW prepared in Example 17.

[0073] Fig.14 This is a test chart of H2O2 production of P / RF-CW prepared in Example 1 and Example 17.

[0074] Fig.15 This is a test diagram of the cyclic stability experiment of the electro-Fenton system in Example 1. DETAILED DESCRIPTION

[0075] In the description of the present invention, it should be understood that descriptions involving orientation, such as orientation or positional relationship indicated as up, down, etc., are based on the orientation or positional relationship shown in the embodiments, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0076] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0077] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.

[0078] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0079] In the embodiments and comparative examples, the electrolyte in the electro-Fenton system is a 50 mM Na2SO4 solution.

[0080] Example 1

[0081] A floating cathode electro-Fenton system, schematic diagram as shown Figure 1 As shown, specifically, it includes a floating cathode, and an anode that forms a lateral reaction system with the floating cathode;

[0082] The floating cathode comprises carbonized pine wood with orderly arranged vertical pores, and phenolic resin and polytetrafluoroethylene loaded in the carbonized pine wood.

[0083] Among them, the thickness of the carbonized pine wood is 2mm.

[0084] The loading amount of the phenolic resin in the carbonized pine wood is 223 mg.

[0085] The loading amount of polytetrafluoroethylene in the carbonized pine wood is 524 mg.

[0086] In the above floating cathode electro-Fenton system, the MMO (metal oxide) electrode is used as the counter electrode and the silver / silver chloride is used as the reference electrode.

[0087] The method for preparing the above-mentioned floating cathode electro-Fenton system comprises the following steps:

[0088] A natural pine wood with a size of 4 cm × 8 cm was selected and cut into 2 mm thick pine wood slices perpendicular to its growth direction. The pine wood slices were placed in a tubular furnace and heat treated in an argon atmosphere. After 6 hours of high-temperature treatment at 800 ° C, the carbonized pine wood was immersed in a mixed solution containing resorcinol, formaldehyde, ammonia water and pure water. The reaction was continued at 250 ° C in a high-temperature reactor for 24 hours, so that phenolic resin was formed in situ in the wood pores. The free phenolic resin and excess precursors were removed by acetone washing to obtain RF-CW.

[0089] The RF-CW was immersed in a polytetrafluoroethylene solution, taken out and dried, and then placed in a muffle furnace at 300°C for 2 hours for heat treatment to obtain a cathode. The schematic diagram of the cathode preparation process is shown in FIG. Figure 2 shown.

[0090] The cathode is coupled to the anode to form a lateral reaction system to obtain the above-mentioned floating cathode electro-Fenton system.

[0091] A method for degrading tetracycline in a solution using the floating cathode electro-Fenton system comprises the following steps:

[0092] A solution containing tetracycline and a catalyst are added to the floating cathode electro-Fenton system to obtain a mixed solution with a pH of 3, which is then electrolyzed to degrade the tetracycline in the solution.

[0093] The above catalyst contains Fe 2+ Compounds, of which Fe 2+ The concentration in the mixed solution is 0.4 mol / L.

[0094] In the above electrolysis process, the applied current was 200 mA and the current density was 20 mA cm -2 .

[0095] Example 2

[0096] The difference between Example 2 and Example 1 is that the thickness of the carbonized pine wood is different. In Example 2, the thickness of the carbonized pine wood is 4 mm.

[0097] A floating cathode electro-Fenton system, comprising a floating cathode and an anode forming a lateral reaction system with the floating cathode;

[0098] The cathode comprises carbonized pine wood with orderly arranged vertical channels, and phenolic resin and polytetrafluoroethylene loaded in the carbonized pine wood.

[0099] Among them, the thickness of the carbonized pine wood is 4mm.

[0100] The loading amount of the phenolic resin in the carbonized pine wood is 223 mg.

[0101] The loading amount of polytetrafluoroethylene in the carbonized pine wood is 524 mg.

[0102] In the above floating cathode electro-Fenton system, the MMO (metal oxide) electrode is used as the counter electrode and the silver / silver chloride is used as the reference electrode.

[0103] The method for preparing the above-mentioned floating cathode electro-Fenton system comprises the following steps:

[0104] A natural pine wood with a size of 4 cm × 8 cm was selected and cut into 2 mm thick pine wood slices perpendicular to its growth direction. The pine wood slices were placed in a tubular furnace and heat treated in an argon atmosphere. After 6 hours of high-temperature treatment at 800 ° C, the carbonized pine wood was immersed in a mixed solution containing resorcinol, formaldehyde, ammonia water and pure water. The reaction was continued at 250 ° C in a high-temperature reactor for 24 hours, so that phenolic resin was formed in situ in the wood pores. The free phenolic resin and excess precursors were removed by acetone washing to obtain RF-CW.

[0105] The RF-CW was immersed in a polytetrafluoroethylene solution, taken out and dried, and then placed in a muffle furnace at 300° C. for 2 hours for heat treatment to obtain a cathode;

[0106] The cathode is coupled to the anode to form a lateral reaction system to obtain the above-mentioned floating cathode electro-Fenton system.

[0107] A method for degrading tetracycline in a solution using the floating cathode electro-Fenton system comprises the following steps:

[0108] A solution containing tetracycline and a catalyst are added to the floating cathode electro-Fenton system to obtain a mixed solution with a pH of 3, which is then electrolyzed to degrade the tetracycline in the solution.

[0109] The above catalyst contains Fe 2+ Compounds, of which Fe 2+ The concentration in the mixed solution is 0.4 mol / L.

[0110] In the above electrolysis process, the applied current was 200 mA and the current density was 20 mA cm -2 .

[0111] Example 3

[0112] The difference between Example 3 and Example 1 is that the thickness of the carbonized pine wood is different. In Example 3, the thickness of the carbonized pine wood is 6 mm.

[0113] A floating cathode electro-Fenton system, comprising a floating cathode and an anode forming a lateral reaction system with the floating cathode;

[0114] The cathode comprises carbonized pine wood with orderly arranged vertical channels, and phenolic resin and polytetrafluoroethylene loaded in the carbonized pine wood.

[0115] Among them, the thickness of the carbonized pine wood is 6mm.

[0116] The loading amount of the phenolic resin in the carbonized pine wood is 223 mg.

[0117] The loading amount of polytetrafluoroethylene in the carbonized pine wood is 524 mg.

[0118] In the above floating cathode electro-Fenton system, the MMO (metal oxide) electrode is used as the counter electrode and the silver / silver chloride is used as the reference electrode.

[0119] The method for preparing the above-mentioned floating cathode electro-Fenton system comprises the following steps:

[0120] A natural pine wood with a size of 4 cm × 8 cm was selected and cut into 2 mm thick pine wood slices perpendicular to its growth direction. The pine wood slices were placed in a tubular furnace and heat treated in an argon atmosphere. After 6 hours of high-temperature treatment at 800 ° C, the carbonized pine wood was immersed in a mixed solution containing resorcinol, formaldehyde, ammonia water and pure water. The reaction was continued at 250 ° C in a high-temperature reactor for 24 hours, so that phenolic resin was formed in situ in the wood pores. The free phenolic resin and excess precursors were removed by acetone washing to obtain RF-CW.

[0121] The RF-CW was immersed in a polytetrafluoroethylene solution, taken out and dried, and then placed in a muffle furnace at 300° C. for 2 hours for heat treatment to obtain a cathode;

[0122] The cathode is coupled to the anode to form a lateral reaction system to obtain the above-mentioned floating cathode electro-Fenton system.

[0123] A method for degrading tetracycline in a solution using the floating cathode electro-Fenton system comprises the following steps:

[0124] A solution containing tetracycline and a catalyst are added to the floating cathode electro-Fenton system to obtain a mixed solution with a pH of 3, which is then electrolyzed to degrade the tetracycline in the solution.

[0125] The above catalyst contains Fe 2+ Compounds, of which Fe 2+ The concentration in the mixed solution is 0.4 mol / L.

[0126] In the above electrolysis process, the applied current was 200 mA and the current density was 20 mA cm -2 .

[0127] Example 4

[0128] The difference between Example 4 and Example 1 is that the loading amount of the phenolic resin in the carbonized pine wood is different. In Example 4, the loading amount of the phenolic resin in the carbonized pine wood is 94 mg.

[0129] A floating cathode electro-Fenton system, comprising a floating cathode and an anode forming a lateral reaction system with the floating cathode;

[0130] The cathode comprises carbonized pine wood with orderly arranged vertical channels, and phenolic resin and polytetrafluoroethylene loaded in the carbonized pine wood.

[0131] Among them, the thickness of the carbonized pine wood is 2mm.

[0132] The loading amount of the phenolic resin in the carbonized pine wood is 94 mg.

[0133] The loading amount of polytetrafluoroethylene in the carbonized pine wood is 524 mg.

[0134] In the above floating cathode electro-Fenton system, the MMO (metal oxide) electrode is used as the counter electrode and the silver / silver chloride is used as the reference electrode.

[0135] The method for preparing the above-mentioned floating cathode electro-Fenton system comprises the following steps:

[0136] A natural pine wood with a size of 4 cm × 8 cm was selected and cut into 2 mm thick pine wood slices perpendicular to its growth direction. The pine wood slices were placed in a tubular furnace and heat treated in an argon atmosphere. After 6 hours of high-temperature treatment at 800 ° C, the carbonized pine wood was immersed in a mixed solution containing resorcinol, formaldehyde, ammonia water and pure water. The reaction was continued at 250 ° C in a high-temperature reactor for 24 hours, so that phenolic resin was formed in situ in the wood pores. The free phenolic resin and excess precursors were removed by acetone washing to obtain RF-CW.

[0137] The RF-CW was immersed in a polytetrafluoroethylene solution, taken out and dried, and then placed in a muffle furnace at 300° C. for 2 hours for heat treatment to obtain a cathode;

[0138] The cathode is coupled to the anode to form a lateral reaction system to obtain the above-mentioned floating cathode electro-Fenton system.

[0139] A method for degrading tetracycline in a solution using the floating cathode electro-Fenton system comprises the following steps:

[0140] A solution containing tetracycline and a catalyst are added to the floating cathode electro-Fenton system to obtain a mixed solution with a pH of 3, which is then electrolyzed to degrade the tetracycline in the solution.

[0141] The above catalyst contains Fe 2+ Compounds, of which Fe 2+ The concentration in the mixed solution is 0.4 mol / L.

[0142] In the above electrolysis process, the applied current was 200 mA and the current density was 20 mA cm -2 .

[0143] Example 5

[0144] The difference between Example 5 and Example 1 is that the loading amount of the phenolic resin in the carbonized pine wood is different. In Example 5, the loading amount of the phenolic resin in the carbonized pine wood is 146 mg.

[0145] A floating cathode electro-Fenton system, comprising a floating cathode and an anode forming a lateral reaction system with the floating cathode;

[0146] The cathode comprises carbonized pine wood with orderly arranged vertical channels, and phenolic resin and polytetrafluoroethylene loaded in the carbonized pine wood.

[0147] Among them, the thickness of the carbonized pine wood is 2mm.

[0148] The loading amount of the phenolic resin in the carbonized pine wood is 146 mg.

[0149] The loading amount of polytetrafluoroethylene in the carbonized pine wood is 524 mg.

[0150] In the above floating cathode electro-Fenton system, the MMO (metal oxide) electrode is used as the counter electrode and the silver / silver chloride is used as the reference electrode.

[0151] The method for preparing the above-mentioned floating cathode electro-Fenton system comprises the following steps:

[0152] A natural pine wood with a size of 4 cm × 8 cm was selected and cut into 2 mm thick pine wood slices perpendicular to its growth direction. The pine wood slices were placed in a tubular furnace and heat treated in an argon atmosphere. After 6 hours of high-temperature treatment at 800 ° C, the carbonized pine wood was immersed in a mixed solution containing resorcinol, formaldehyde, ammonia water and pure water. The reaction was continued at 250 ° C in a high-temperature reactor for 24 hours, so that phenolic resin was formed in situ in the wood pores. The free phenolic resin and excess precursors were removed by acetone washing to obtain RF-CW.

[0153] The RF-CW was immersed in a polytetrafluoroethylene solution, taken out and dried, and then placed in a muffle furnace at 300° C. for 2 hours for heat treatment to obtain a cathode;

[0154] The cathode is coupled to the anode to form a lateral reaction system to obtain the above-mentioned floating cathode electro-Fenton system.

[0155] A method for degrading tetracycline in a solution using the floating cathode electro-Fenton system comprises the following steps:

[0156] A solution containing tetracycline and a catalyst are added to the floating cathode electro-Fenton system to obtain a mixed solution with a pH of 3, which is then electrolyzed to degrade the tetracycline in the solution.

[0157] The above catalyst contains Fe 2+ Compounds, of which Fe 2+ The concentration in the mixed solution is 0.4 mol / L.

[0158] In the above electrolysis process, the applied current was 200 mA and the current density was 20 mA cm -2 .

[0159] Example 6

[0160] The difference between Example 6 and Example 1 is that the loading amount of polytetrafluoroethylene in the carbonized pine wood is different. In Example 6, the loading amount of polytetrafluoroethylene in the carbonized pine wood is 391 mg.

[0161] A floating cathode electro-Fenton system, comprising a floating cathode and an anode forming a lateral reaction system with the floating cathode;

[0162] The cathode comprises carbonized pine wood with orderly arranged vertical channels, and phenolic resin and polytetrafluoroethylene loaded in the carbonized pine wood.

[0163] Among them, the thickness of the carbonized pine wood is 2mm.

[0164] The loading amount of the phenolic resin in the carbonized pine wood is 223 mg.

[0165] The loading amount of polytetrafluoroethylene in the carbonized pine wood is 391 mg.

[0166] In the above floating cathode electro-Fenton system, the MMO (metal oxide) electrode is used as the counter electrode and the silver / silver chloride is used as the reference electrode.

[0167] The method for preparing the above-mentioned floating cathode electro-Fenton system comprises the following steps:

[0168] A natural pine wood with a size of 4 cm × 8 cm was selected and cut into 2 mm thick pine wood slices perpendicular to its growth direction. The pine wood slices were placed in a tubular furnace and heat treated in an argon atmosphere. After 6 hours of high-temperature treatment at 800 ° C, the carbonized pine wood was immersed in a mixed solution containing resorcinol, formaldehyde, ammonia water and pure water. The reaction was continued at 250 ° C in a high-temperature reactor for 24 hours, so that phenolic resin was formed in situ in the wood pores. The free phenolic resin and excess precursors were removed by acetone washing to obtain RF-CW.

[0169] The RF-CW was immersed in a polytetrafluoroethylene solution, taken out and dried, and then placed in a muffle furnace at 300° C. for 2 hours for heat treatment to obtain a cathode;

[0170] The cathode is coupled to the anode to form a lateral reaction system to obtain the above-mentioned floating cathode electro-Fenton system.

[0171] A method for degrading tetracycline in a solution using the floating cathode electro-Fenton system comprises the following steps:

[0172] A solution containing tetracycline and a catalyst are added to the floating cathode electro-Fenton system to obtain a mixed solution with a pH of 3, which is then electrolyzed to degrade the tetracycline in the solution.

[0173] The above catalyst contains Fe 2+ Compounds, of which Fe 2+ The concentration in the mixed solution is 0.4 mol / L.

[0174] In the above electrolysis process, the applied current was 200 mA and the current density was 20 mA cm -2 .

[0175] Example 7

[0176] The difference between Example 7 and Example 1 is that the loading amount of polytetrafluoroethylene in the carbonized pine wood is different. In Example 7, the loading amount of polytetrafluoroethylene in the carbonized pine wood is 780 mg.

[0177] A floating cathode electro-Fenton system, comprising a floating cathode and an anode forming a lateral reaction system with the floating cathode;

[0178] The cathode comprises carbonized pine wood with orderly arranged vertical channels, and phenolic resin and polytetrafluoroethylene loaded in the carbonized pine wood.

[0179] Among them, the thickness of the carbonized pine wood is 2mm.

[0180] The loading amount of the phenolic resin in the carbonized pine wood is 223 mg.

[0181] The loading amount of polytetrafluoroethylene in the carbonized pine wood is 780 mg.

[0182] In the above floating cathode electro-Fenton system, the MMO (metal oxide) electrode is used as the counter electrode and the silver / silver chloride is used as the reference electrode.

[0183] The method for preparing the above-mentioned floating cathode electro-Fenton system comprises the following steps:

[0184] A natural pine wood with a size of 4 cm × 8 cm was selected and cut into 2 mm thick pine wood slices perpendicular to its growth direction. The pine wood slices were placed in a tubular furnace and heat treated in an argon atmosphere. After 6 hours of high-temperature treatment at 800 ° C, the carbonized pine wood was immersed in a mixed solution containing resorcinol, formaldehyde, ammonia water and pure water. The reaction was continued at 250 ° C in a high-temperature reactor for 24 hours, so that phenolic resin was formed in situ in the wood pores. The free phenolic resin and excess precursors were removed by acetone washing to obtain RF-CW.

[0185] The RF-CW was immersed in a polytetrafluoroethylene solution, taken out and dried, and then placed in a muffle furnace at 300° C. for 2 hours for heat treatment to obtain a cathode;

[0186] The cathode is coupled to the anode to form a lateral reaction system to obtain the above-mentioned floating cathode electro-Fenton system.

[0187] A method for degrading tetracycline in a solution using the floating cathode electro-Fenton system comprises the following steps:

[0188] A solution containing tetracycline and a catalyst are added to the floating cathode electro-Fenton system to obtain a mixed solution with a pH of 3, which is then electrolyzed to degrade the tetracycline in the solution.

[0189] The above catalyst contains Fe 2+ Compounds, of which Fe 2+ The concentration in the mixed solution is 0.4 mol / L.

[0190] In the above electrolysis process, the applied current was 200 mA and the current density was 20 mA cm -2 .

[0191] Example 8

[0192] The difference between Example 8 and Example 1 is that the current density during the electrolysis process is different. The current density of Example 8 is 10 mA cm -2 .

[0193] A floating cathode electro-Fenton system, comprising a floating cathode and an anode forming a lateral reaction system with the floating cathode;

[0194] The cathode comprises carbonized pine wood with orderly arranged vertical channels, and phenolic resin and polytetrafluoroethylene loaded in the carbonized pine wood.

[0195] Among them, the thickness of the carbonized pine wood is 2mm.

[0196] The loading amount of the phenolic resin in the carbonized pine wood is 223 mg.

[0197] The loading amount of polytetrafluoroethylene in the carbonized pine wood is 524 mg.

[0198] In the above floating cathode electro-Fenton system, the MMO (metal oxide) electrode is used as the counter electrode and the silver / silver chloride is used as the reference electrode.

[0199] The method for preparing the above-mentioned floating cathode electro-Fenton system comprises the following steps:

[0200] A natural pine wood with a size of 4 cm × 8 cm was selected and cut into 2 mm thick pine wood slices perpendicular to its growth direction. The pine wood slices were placed in a tubular furnace and heat treated in an argon atmosphere. After 6 hours of high-temperature treatment at 800 ° C, the carbonized pine wood was immersed in a mixed solution containing resorcinol, formaldehyde, ammonia water and pure water. The reaction was continued at 250 ° C in a high-temperature reactor for 24 hours, so that phenolic resin was formed in situ in the wood pores. The free phenolic resin and excess precursors were removed by acetone washing to obtain RF-CW.

[0201] The RF-CW was immersed in a polytetrafluoroethylene solution, taken out and dried, and then placed in a muffle furnace at 300° C. for 2 hours for heat treatment to obtain a cathode;

[0202] The cathode is coupled to the anode to form a lateral reaction system to obtain the above-mentioned floating cathode electro-Fenton system.

[0203] A method for degrading tetracycline in a solution using the floating cathode electro-Fenton system comprises the following steps:

[0204] A solution containing tetracycline and a catalyst are added to the floating cathode electro-Fenton system to obtain a mixed solution with a pH of 3, which is then electrolyzed to degrade the tetracycline in the solution.

[0205] The above catalyst contains Fe 2+ Compounds, of which Fe 2+ The concentration in the mixed solution is 0.4 mol / L.

[0206] In the above electrolysis process, the applied current was 200 mA and the current density was 10 mA cm -2 .

[0207] Example 9

[0208] The difference between Example 9 and Example 1 is that the current density during the electrolysis process is different. The current density of Example 9 is 15 mA cm -2 .

[0209] A floating cathode electro-Fenton system, comprising a floating cathode and an anode forming a lateral reaction system with the floating cathode;

[0210] The cathode comprises carbonized pine wood with orderly arranged vertical channels, and phenolic resin and polytetrafluoroethylene loaded in the carbonized pine wood.

[0211] Among them, the thickness of the carbonized pine wood is 2mm.

[0212] The loading amount of the phenolic resin in the carbonized pine wood is 223 mg.

[0213] The loading amount of polytetrafluoroethylene in the carbonized pine wood is 524 mg.

[0214] In the above floating cathode electro-Fenton system, the MMO (metal oxide) electrode is used as the counter electrode and the silver / silver chloride is used as the reference electrode.

[0215] The method for preparing the above-mentioned floating cathode electro-Fenton system comprises the following steps:

[0216] A natural pine wood with a size of 4 cm × 8 cm was selected and cut into 2 mm thick pine wood slices perpendicular to its growth direction. The pine wood slices were placed in a tubular furnace and heat treated in an argon atmosphere. After 6 hours of high-temperature treatment at 800 ° C, the carbonized pine wood was immersed in a mixed solution containing resorcinol, formaldehyde, ammonia water and pure water. The reaction was continued at 250 ° C in a high-temperature reactor for 24 hours, so that phenolic resin was formed in situ in the wood pores. The free phenolic resin and excess precursors were removed by acetone washing to obtain RF-CW.

[0217] The RF-CW was immersed in a polytetrafluoroethylene solution, taken out and dried, and then placed in a muffle furnace at 300° C. for 2 hours for heat treatment to obtain a cathode;

[0218] The cathode is coupled to the anode to form a lateral reaction system to obtain the above-mentioned floating cathode electro-Fenton system.

[0219] A method for degrading tetracycline in a solution using the floating cathode electro-Fenton system comprises the following steps:

[0220] A solution containing tetracycline and a catalyst are added to the floating cathode electro-Fenton system to obtain a mixed solution with a pH of 3, which is then electrolyzed to degrade the tetracycline in the solution.

[0221] The above catalyst contains Fe 2+ Compounds, of which Fe 2+ The concentration in the mixed solution is 0.4 mol / L.

[0222] In the above electrolysis process, the applied current was 200 mA and the current density was 15 mA cm -2 .

[0223] Example 10

[0224] The difference between Example 10 and Example 1 is that the current during the electrolysis process is different. The current of Example 10 is 100 mA.

[0225] A floating cathode electro-Fenton system, comprising a floating cathode and an anode forming a lateral reaction system with the floating cathode;

[0226] The cathode comprises carbonized pine wood with orderly arranged vertical channels, and phenolic resin and polytetrafluoroethylene loaded in the carbonized pine wood.

[0227] Among them, the thickness of the carbonized pine wood is 2mm.

[0228] The loading amount of the phenolic resin in the carbonized pine wood is 223 mg.

[0229] The loading amount of polytetrafluoroethylene in the carbonized pine wood is 524 mg.

[0230] In the above floating cathode electro-Fenton system, the MMO (metal oxide) electrode is used as the counter electrode and the silver / silver chloride is used as the reference electrode.

[0231] The method for preparing the above-mentioned floating cathode electro-Fenton system comprises the following steps:

[0232] A natural pine wood with a size of 4 cm × 8 cm was selected and cut into 2 mm thick pine wood slices perpendicular to its growth direction. The pine wood slices were placed in a tubular furnace and heat treated in an argon atmosphere. After 6 hours of high-temperature treatment at 800 ° C, the carbonized pine wood was immersed in a mixed solution containing resorcinol, formaldehyde, ammonia water and pure water. The reaction was continued at 250 ° C in a high-temperature reactor for 24 hours, so that phenolic resin was formed in situ in the wood pores. The free phenolic resin and excess precursors were removed by acetone washing to obtain RF-CW.

[0233] The RF-CW was immersed in a polytetrafluoroethylene solution, taken out and dried, and then placed in a muffle furnace at 300° C. for 2 hours for heat treatment to obtain a cathode;

[0234] The cathode is coupled to the anode to form a lateral reaction system to obtain the above-mentioned floating cathode electro-Fenton system.

[0235] A method for degrading tetracycline in a solution using the floating cathode electro-Fenton system comprises the following steps:

[0236] A solution containing tetracycline and a catalyst are added to the floating cathode electro-Fenton system to obtain a mixed solution with a pH of 3, which is then electrolyzed to degrade the tetracycline in the solution.

[0237] The above catalyst contains Fe 2+ Compounds, of which Fe 2+ The concentration in the mixed solution is 0.4 mol / L.

[0238] In the above electrolysis process, the applied current was 100 mA and the current density was 20 mA cm -2 .

[0239] Embodiment 11

[0240] The difference between Example 11 and Example 1 is that the current during the electrolysis process is different. The current of Example 11 is 150 mA.

[0241] A floating cathode electro-Fenton system, comprising a floating cathode and an anode forming a lateral reaction system with the floating cathode;

[0242] The cathode comprises carbonized pine wood with orderly arranged vertical channels, and phenolic resin and polytetrafluoroethylene loaded in the carbonized pine wood.

[0243] Among them, the thickness of the carbonized pine wood is 2mm.

[0244] The loading amount of the phenolic resin in the carbonized pine wood is 223 mg.

[0245] The loading amount of polytetrafluoroethylene in the carbonized pine wood is 524 mg.

[0246] In the above floating cathode electro-Fenton system, the MMO (metal oxide) electrode is used as the counter electrode and the silver / silver chloride is used as the reference electrode.

[0247] The method for preparing the above-mentioned floating cathode electro-Fenton system comprises the following steps:

[0248] A natural pine wood with a size of 4 cm × 8 cm was selected and cut into 2 mm thick pine wood slices perpendicular to its growth direction. The pine wood slices were placed in a tubular furnace and heat treated in an argon atmosphere. After 6 hours of high-temperature treatment at 800 ° C, the carbonized pine wood was immersed in a mixed solution containing resorcinol, formaldehyde, ammonia water and pure water. The reaction was continued at 250 ° C in a high-temperature reactor for 24 hours, so that phenolic resin was formed in situ in the wood pores. The free phenolic resin and excess precursors were removed by acetone washing to obtain RF-CW.

[0249] The RF-CW was immersed in a polytetrafluoroethylene solution, taken out and dried, and then placed in a muffle furnace at 300° C. for 2 hours for heat treatment to obtain a cathode;

[0250] The cathode is coupled to the anode to form a lateral reaction system to obtain the above-mentioned floating cathode electro-Fenton system.

[0251] A method for degrading tetracycline in a solution using the floating cathode electro-Fenton system comprises the following steps:

[0252] A solution containing tetracycline and a catalyst are added to the floating cathode electro-Fenton system to obtain a mixed solution with a pH of 3, which is then electrolyzed to degrade the tetracycline in the solution.

[0253] The above catalyst contains Fe 2+ Compounds, of which Fe 2+ The concentration in the mixed solution is 0.4 mol / L.

[0254] In the above electrolysis process, the applied current was 150 mA and the current density was 20 mA cm -2 .

[0255] Example 12

[0256] The difference between Example 12 and Example 1 is that Fe 2+ The concentrations of Fe in the mixed solution are different. 2+ The concentration in the mixed solution is 0 mol / L.

[0257] A floating cathode electro-Fenton system, comprising a floating cathode and an anode forming a lateral reaction system with the floating cathode;

[0258] The cathode comprises carbonized pine wood with orderly arranged vertical channels, and phenolic resin and polytetrafluoroethylene loaded in the carbonized pine wood.

[0259] Among them, the thickness of the carbonized pine wood is 2mm.

[0260] The loading amount of the phenolic resin in the carbonized pine wood is 223 mg.

[0261] The loading amount of polytetrafluoroethylene in the carbonized pine wood is 524 mg.

[0262] In the above floating cathode electro-Fenton system, the MMO (metal oxide) electrode is used as the counter electrode and the silver / silver chloride is used as the reference electrode.

[0263] The method for preparing the above-mentioned floating cathode electro-Fenton system comprises the following steps:

[0264] A natural pine wood with a size of 4 cm × 8 cm was selected and cut into 2 mm thick pine wood slices perpendicular to its growth direction. The pine wood slices were placed in a tubular furnace and heat treated in an argon atmosphere. After 6 hours of high-temperature treatment at 800 ° C, the carbonized pine wood was immersed in a mixed solution containing resorcinol, formaldehyde, ammonia water and pure water. The reaction was continued at 250 ° C in a high-temperature reactor for 24 hours, so that phenolic resin was formed in situ in the wood pores. The free phenolic resin and excess precursors were removed by acetone washing to obtain RF-CW.

[0265] The RF-CW was immersed in a polytetrafluoroethylene solution, taken out and dried, and then placed in a muffle furnace at 300° C. for 2 hours for heat treatment to obtain a cathode;

[0266] The cathode is coupled to the anode to form a lateral reaction system to obtain the above-mentioned floating cathode electro-Fenton system.

[0267] A method for degrading tetracycline in a solution using the floating cathode electro-Fenton system comprises the following steps:

[0268] A solution containing tetracycline is added to the floating cathode electro-Fenton system to obtain a mixed solution with a pH of 3, and the mixed solution is electrolyzed to degrade the tetracycline in the solution.

[0269] In the above electrolysis process, the applied current was 200 mA and the current density was 20 mA cm -2 .

[0270] Example 13

[0271] The difference between Example 13 and Example 1 is that Fe 2+ The concentrations of Fe in the mixed solution are different. 2+ The concentration in the mixed solution is 0.2 mol / L.

[0272] A floating cathode electro-Fenton system, comprising a floating cathode and an anode forming a lateral reaction system with the floating cathode;

[0273] The cathode comprises carbonized pine wood with orderly arranged vertical channels, and phenolic resin and polytetrafluoroethylene loaded in the carbonized pine wood.

[0274] Among them, the thickness of the carbonized pine wood is 2mm.

[0275] The loading amount of the phenolic resin in the carbonized pine wood is 223 mg.

[0276] The loading amount of polytetrafluoroethylene in the carbonized pine wood is 524 mg.

[0277] In the above floating cathode electro-Fenton system, the MMO (metal oxide) electrode is used as the counter electrode and the silver / silver chloride is used as the reference electrode.

[0278] The method for preparing the above-mentioned floating cathode electro-Fenton system comprises the following steps:

[0279] A natural pine wood with a size of 4 cm × 8 cm was selected and cut into 2 mm thick pine wood slices perpendicular to its growth direction. The pine wood slices were placed in a tubular furnace and heat treated in an argon atmosphere. After 6 hours of high-temperature treatment at 800 ° C, the carbonized pine wood was immersed in a mixed solution containing resorcinol, formaldehyde, ammonia water and pure water. The reaction was continued at 250 ° C in a high-temperature reactor for 24 hours, so that phenolic resin was formed in situ in the wood pores. The free phenolic resin and excess precursors were removed by acetone washing to obtain RF-CW.

[0280] The RF-CW was immersed in a polytetrafluoroethylene solution, taken out and dried, and then placed in a muffle furnace at 300° C. for 2 hours for heat treatment to obtain a cathode;

[0281] The cathode is coupled to the anode to form a lateral reaction system to obtain the above-mentioned floating cathode electro-Fenton system.

[0282] A method for degrading tetracycline in a solution using the floating cathode electro-Fenton system comprises the following steps:

[0283] A solution containing tetracycline and a catalyst are added to the floating cathode electro-Fenton system to obtain a mixed solution with a pH of 3, which is then electrolyzed to degrade the tetracycline in the solution.

[0284] The above catalyst contains Fe 2+ Compounds, of which Fe 2+ The concentration in the mixed solution is 0.2 mol / L.

[0285] In the above electrolysis process, the applied current was 200 mA and the current density was 20 mA cm -2 .

[0286] Embodiment 14

[0287] The difference between Example 14 and Example 1 is that the pH of the mixed solution is different. In Example 14, the pH of the mixed solution is 1.

[0288] A floating cathode electro-Fenton system, comprising a floating cathode and an anode forming a lateral reaction system with the floating cathode;

[0289] The cathode comprises carbonized pine wood with orderly arranged vertical channels, and phenolic resin and polytetrafluoroethylene loaded in the carbonized pine wood.

[0290] Among them, the thickness of the carbonized pine wood is 2mm.

[0291] The loading amount of the phenolic resin in the carbonized pine wood is 223 mg.

[0292] The loading amount of polytetrafluoroethylene in the carbonized pine wood is 524 mg.

[0293] In the above floating cathode electro-Fenton system, the MMO (metal oxide) electrode is used as the counter electrode and the silver / silver chloride is used as the reference electrode.

[0294] The method for preparing the above-mentioned floating cathode electro-Fenton system comprises the following steps:

[0295] A natural pine wood with a size of 4 cm × 8 cm was selected and cut into 2 mm thick pine wood slices perpendicular to its growth direction. The pine wood slices were placed in a tubular furnace and heat treated in an argon atmosphere. After 6 hours of high-temperature treatment at 800 ° C, the carbonized pine wood was immersed in a mixed solution containing resorcinol, formaldehyde, ammonia water and pure water. The reaction was continued at 250 ° C in a high-temperature reactor for 24 hours, so that phenolic resin was formed in situ in the wood pores. The free phenolic resin and excess precursors were removed by acetone washing to obtain RF-CW.

[0296] The RF-CW was immersed in a polytetrafluoroethylene solution, taken out and dried, and then placed in a muffle furnace at 300° C. for 2 hours for heat treatment to obtain a cathode;

[0297] The cathode is coupled to the anode to form a lateral reaction system to obtain the above-mentioned floating cathode electro-Fenton system.

[0298] A method for degrading tetracycline in a solution using the floating cathode electro-Fenton system comprises the following steps:

[0299] A solution containing tetracycline and a catalyst are added to the floating cathode electro-Fenton system to obtain a mixed solution with a pH of 1, which is then electrolyzed to degrade the tetracycline in the solution.

[0300] The above catalyst contains Fe 2+ Compounds, of which Fe 2+ The concentration in the mixed solution is 0.4 mol / L.

[0301] In the above electrolysis process, the applied current was 200 mA and the current density was 20 mA cm -2 .

[0302] Embodiment 15

[0303] The difference between Example 15 and Example 1 is that the pH of the mixed solution is different. In Example 15, the pH of the mixed solution is 5.

[0304] A floating cathode electro-Fenton system, comprising a floating cathode and an anode forming a lateral reaction system with the floating cathode;

[0305] The cathode comprises carbonized pine wood with orderly arranged vertical channels, and phenolic resin and polytetrafluoroethylene loaded in the carbonized pine wood.

[0306] Among them, the thickness of the carbonized pine wood is 2mm.

[0307] The loading amount of the phenolic resin in the carbonized pine wood is 223 mg.

[0308] The loading amount of polytetrafluoroethylene in the carbonized pine wood is 524 mg.

[0309] In the above floating cathode electro-Fenton system, the MMO (metal oxide) electrode is used as the counter electrode and the silver / silver chloride is used as the reference electrode.

[0310] The method for preparing the above-mentioned floating cathode electro-Fenton system comprises the following steps:

[0311] A natural pine wood with a size of 4 cm × 8 cm was selected and cut into 2 mm thick pine wood slices perpendicular to its growth direction. The pine wood slices were placed in a tubular furnace and heat treated in an argon atmosphere. After 6 hours of high-temperature treatment at 800 ° C, the carbonized pine wood was immersed in a mixed solution containing resorcinol, formaldehyde, ammonia water and pure water. The reaction was continued at 250 ° C in a high-temperature reactor for 24 hours, so that phenolic resin was formed in situ in the wood pores. The free phenolic resin and excess precursors were removed by acetone washing to obtain RF-CW.

[0312] The RF-CW was immersed in a polytetrafluoroethylene solution, taken out and dried, and then placed in a muffle furnace at 300° C. for 2 hours for heat treatment to obtain a cathode;

[0313] The cathode is coupled to the anode to form a lateral reaction system to obtain the above-mentioned floating cathode electro-Fenton system.

[0314] A method for degrading tetracycline in a solution using the floating cathode electro-Fenton system comprises the following steps:

[0315] A solution containing tetracycline and a catalyst are added to the floating cathode electro-Fenton system to obtain a mixed solution with a pH of 5, which is then electrolyzed to degrade the tetracycline in the solution.

[0316] The above catalyst contains Fe 2+ Compounds, of which Fe 2+ The concentration in the mixed solution is 0.4 mol / L.

[0317] In the above electrolysis process, the applied current was 200 mA and the current density was 20 mA cm -2 .

[0318] Example 16

[0319] The difference between Example 16 and Example 1 is that in the floating cathode electro-Fenton system, a Ti electrode is used as a counter electrode.

[0320] A floating cathode electro-Fenton system, comprising a floating cathode and an anode forming a lateral reaction system with the floating cathode;

[0321] The cathode comprises carbonized pine wood with orderly arranged vertical channels, and phenolic resin and polytetrafluoroethylene loaded in the carbonized pine wood.

[0322] Among them, the thickness of the carbonized pine wood is 2mm.

[0323] The loading amount of the phenolic resin in the carbonized pine wood is 223 mg.

[0324] The loading amount of polytetrafluoroethylene in the carbonized pine wood is 524 mg.

[0325] In the above floating cathode electro-Fenton system, the Ti plate is used as the counter electrode and the silver / silver chloride is used as the reference electrode.

[0326] The method for preparing the above-mentioned floating cathode electro-Fenton system comprises the following steps:

[0327] A natural pine wood with a size of 4 cm × 8 cm was selected and cut into 2 mm thick pine wood slices perpendicular to its growth direction. The pine wood slices were placed in a tubular furnace and heat treated in an argon atmosphere. After 6 hours of high-temperature treatment at 800 ° C, the carbonized pine wood was immersed in a mixed solution containing resorcinol, formaldehyde, ammonia water and pure water. The reaction was continued at 250 ° C in a high-temperature reactor for 24 hours, so that phenolic resin was formed in situ in the wood pores. The free phenolic resin and excess precursors were removed by acetone washing to obtain RF-CW.

[0328] The RF-CW was immersed in a polytetrafluoroethylene solution, taken out and dried, and then placed in a muffle furnace at 300° C. for 2 hours for heat treatment to obtain a cathode;

[0329] The cathode is coupled to the anode to form a lateral reaction system to obtain the above-mentioned floating cathode electro-Fenton system.

[0330] A method for degrading tetracycline in a solution using the floating cathode electro-Fenton system comprises the following steps:

[0331] A solution containing tetracycline and a catalyst are added to the floating cathode electro-Fenton system to obtain a mixed solution with a pH of 3, which is then electrolyzed to degrade the tetracycline in the solution.

[0332] The above catalyst contains Fe 2+ Compounds, of which Fe 2+ The concentration in the mixed solution is 0.4 mol / L.

[0333] In the above electrolysis process, the applied current was 200 mA and the current density was 20 mA cm -2 .

[0334] Embodiment 17

[0335] The difference between Example 17 and Example 1 is that in Example 17, when preparing the floating cathode electro-Fenton system, the carbonized pine wood is directly immersed in phenolic resin to obtain RF-CW with the same loading amount as that in Example 1.

[0336] A floating cathode electro-Fenton system, comprising a floating cathode and an anode forming a lateral reaction system with the floating cathode;

[0337] The cathode comprises carbonized pine wood with orderly arranged vertical channels, and phenolic resin and polytetrafluoroethylene loaded in the carbonized pine wood.

[0338] Among them, the thickness of the carbonized pine wood is 2mm.

[0339] The loading amount of the phenolic resin in the carbonized pine wood is 223 mg.

[0340] The loading amount of polytetrafluoroethylene in the carbonized pine wood is 524 mg.

[0341] In the above floating cathode electro-Fenton system, the MMO (metal oxide) electrode is used as the counter electrode and the silver / silver chloride is used as the reference electrode.

[0342] The method for preparing the above-mentioned floating cathode electro-Fenton system comprises the following steps:

[0343] A natural pine wood with a size of 4 cm × 8 cm was selected and cut into 2 mm thick pine wood slices perpendicular to its growth direction. The pine wood slices were placed in a tubular furnace and heat treated in an argon atmosphere. After 6 hours of high-temperature treatment at 800 ° C, the pine wood was carbonized. The carbonized pine wood was immersed in a solution containing phenolic resin, and the free phenolic resin was removed by washing with acetone to obtain RF-CW.

[0344] The RF-CW was immersed in a polytetrafluoroethylene solution, taken out, dried, and then placed in a muffle furnace at 300° C. for 2 hours for heat treatment to obtain a cathode.

[0345] The cathode is coupled to the anode to form a lateral reaction system to obtain the above-mentioned floating cathode electro-Fenton system.

[0346] A method for degrading tetracycline in a solution using the floating cathode electro-Fenton system comprises the following steps:

[0347] A solution containing tetracycline and a catalyst are added to the floating cathode electro-Fenton system to obtain a mixed solution with a pH of 3, which is then electrolyzed to degrade the tetracycline in the solution.

[0348] The above catalyst contains Fe 2+ Compounds, of which Fe 2+ The concentration in the mixed solution is 0.4 mol / L.

[0349] In the above electrolysis process, the applied current was 200 mA and the current density was 20 mA cm -2 .

[0350] Comparative Example 1

[0351] The difference between Comparative Example 1 and Example 1 is that the floating cathode in Comparative Example 1 is carbonized pine wood with orderly arranged vertical pores, but phenolic resin and polytetrafluoroethylene are not loaded thereon.

[0352] Comparative Example 2

[0353] The difference between Comparative Example 2 and Example 1 is that the floating cathode of Comparative Example 2 is carbonized pine wood with orderly arranged vertical pores loaded with phenolic resin, but polytetrafluoroethylene is not loaded on the carbonized pine wood.

[0354] Comparative Example 3

[0355] The difference between Comparative Example 3 and Example 1 is that the floating cathode of Comparative Example 3 is carbonized pine wood with orderly arranged vertical pores loaded with polytetrafluoroethylene, but phenolic resin is not loaded on the carbonized pine wood.

[0356] Comparative Example 4

[0357] The difference between Comparative Example 4 and Example 1 is that Comparative Example 3 does not use a floating cathode, and the cathode of Comparative Example 3 is immersed in the electrolyte.

[0358] Performance Test:

[0359] The H2O2 yield test of the electro-Fenton system of Examples 1-17 and Comparative Examples 1-4 was performed as follows: The H2O2 concentration was determined by cerium sulfate spectrophotometry. During the experiment, 0.2 mL of sample was taken every 10 minutes in 4 mL of 0.5 mM cerium sulfate solution. After the reaction was complete, the absorbance was measured at a wavelength of 318 nm using a UV-visible spectrophotometer. The tetracycline concentration was determined by high performance liquid chromatography. A C18 chromatographic column was used, equipped with an ultraviolet fluorescence detector at 280 nm, an injection volume of 50 μL, a mobile phase of methanol: water (1 wt% formic acid) = 70:30, a flow rate of 1 mL / min, a column temperature of 30°C, and a detection wavelength of 270 nm.

[0360] The difference between Examples 1-3 is the thickness of the carbonized pine wood. The H2O2 yield test of Examples 1-3 is as follows: Figure 3 As shown, it can be known that a carbonized pine wood thickness of 2 mm is more conducive to the production of H2O2.

[0361] The difference between Example 1 and Examples 4-5 is that the loading amount of phenolic resin in the carbonized pine wood is different. The H2O2 yield test of Example 1 and Examples 4-5 is as follows: Figure 4 shown.

[0362] The difference between Example 1 and Examples 6-7 is that the loading amount of polytetrafluoroethylene in the carbonized pine wood is different. The H2O2 yield test of Example 1 and Examples 6-7 is as follows: Figure 5 As shown, where concentration is the concentration.

[0363] Figure 5 The results show that the H2O2 production reaches a peak at a PTFE loading of 524 mg. When the PTFE loading is reduced to 391 mg, the generated H2O2 concentration decreases to 383.1 mg·L -1 This phenomenon can be attributed to the decrease in the hydrophobicity of the electrode material, which allows liquid to penetrate into the internal pores, thereby hindering the transport of O2 inside the electrode. However, when the PTFE loading was further increased to 780 mg, a significant decrease in H2O2 production was observed, which dropped sharply to only 175.6 mg·L -1 .

[0364] The contact angle test diagrams of Example 1 and Example 6-7 are as follows: Figure 6 As shown, Figure 6 (a) corresponds to the polytetrafluoroethylene loading of Example 6, Figure 6 (b) corresponds to the loading amount of Example 1, Figure 6 (c) corresponds to the loading amount of Example 7. Although the hydrophobic design can enhance the diffusion of O2 and achieve a rich three-phase interface, thereby synergistically improving the performance, the excessive use of PTFE coating may hinder the e- Therefore, finding the optimal PTFE loading is of vital importance for optimizing the electrocatalytic efficiency.

[0365] The difference between Example 1 and Examples 10-11 is that the currents are different during the electrolysis process. The H2O2 yield test of Example 1 and Examples 10-11 is as follows: Figure 7 shown.

[0366] The difference between Example 1 and Examples 12-13 is that Fe 2+ The concentrations in the mixed solution are different.

[0367] The H2O2 yields of Example 1 and Example 12-13 were tested as follows: Figure 8 shown.

[0368] The difference between Example 1 and Examples 14-15 is that the pH of the mixed solution is different. The H2O2 yield test of Example 1 and Examples 14-15 is as follows: Fig. 9 shown.

[0369] The difference between Example 1, Example 16 and Comparative Example 4 is that the cathode position or the counter electrode is different. Specifically, Example 1 uses a floating cathode, and the cathode floats on the surface of the electrolyte, the cathode of Comparative Example 4 is directly immersed in the electrolyte, and Example 16 uses a floating cathode but uses a Ti plate with low OER catalytic activity as the counter electrode to limit the amount of O2 produced by the anode OER.

[0370] The H2O2 yields of Example 1, Example 16 and Comparative Example 4 were tested as follows: Fig.10 As shown. Fig.10 It can be seen that in Comparative Example 4, since the cathode is immersed in the electrolyte, the H2O2 production efficiency is significantly lower than that of Example 1. In Example 16, by limiting the amount of O2 produced by the anode OER, the anode oxygen production is reduced, resulting in a decrease in the H2O2 production of Example 16. By comparing Example 1 with Example 16, it can be proved that the high H2O2 production of the cathode in Example 1 is synergistically supported by the oxygen production of OER and the oxygen in the air, and its pore structure can effectively transmit oxygen in the upper and lower channels, that is, the structure of the electro-Fenton system of the present invention can better utilize the upper and lower oxygen at the same time.

[0371] Among them, the H2O2 yield test of Example 1 and Comparative Examples 1-3 is as follows Fig.11 shown.

[0372] The difference between Example 1 and Example 17 is that Example 1 uses an in-situ hydrothermal method to load phenolic resin in carbonized pine wood, while Example 17 uses a direct impregnation method of phenolic resin to load phenolic resin in carbonized pine wood. Fig.12This is the SEM image of the P / RF-CW prepared in Example 1. It can be seen from the image that the phenolic resin is evenly distributed inside the pores of the carbonized pine wood. Fig.13 This is the SEM image of P / RF-CW prepared in Example 17. It can be seen from the figure that the phenolic resin is not evenly distributed inside the pores. Since the phenolic resin is insoluble in water, the impregnation method of Example 17 requires stirring. After stirring, the pore structure inside the wood will suffer a certain degree of damage, making it difficult for the phenolic resin to be evenly distributed inside the pores. Fig.14 This is a test diagram of H2O2 production of P / RF-CW prepared in Example 1 and Example 17, wherein Example 1 adopts a hydrothermal method and Example 17 adopts an immersion method.

[0373] The electrode stability test was conducted using the floating cathode electro-Fenton system of Example 1, and seven cycle stability experiments were performed, during which the electrolyte was replaced every 60 minutes. Fig.15 As shown, the H2O2 yield is basically maintained at 467.6 mg·L -1 ·h -1 , which reflects the operational stability of the process.

[0374] The above are only embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A floating cathode electro-Fenton system, characterized in that: It comprises a floating cathode and an anode which forms a lateral reaction system with the floating cathode; The floating cathode includes carbonized wood with orderly arranged vertical pores, and phenolic resin and hydrophobic organic polymer loaded in the carbonized wood.

2. A floating cathode electro-Fenton system according to claim 1, characterized in that: The floating cathode floats above the solution to be treated, and the anode is placed below the solution to be treated to form a horizontal reactor.

3. A floating cathode electro-Fenton system according to claim 1, characterized in that: The mass ratio of the phenolic resin and the hydrophobic organic polymer loaded in the carbonized wood is 16-110:391-780.

4. A floating cathode electro-Fenton system according to claim 1, characterized in that: The carbonized wood includes carbonized pine wood.

5. A method for preparing a floating cathode electro-Fenton system as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: After carbonizing the wood, it is immersed in a phenolic resin precursor solution. After a hydrothermal reaction, the phenolic resin is in situ formed in the pores of the wood to obtain RF-CW. The RF-CW is immersed in a hydrophobic organic polymer solution, taken out, dried, and then heat-treated to obtain a floating cathode; The floating cathode is coupled to the anode to form a lateral reaction system to obtain the floating cathode electro-Fenton system.

6. The method according to claim 5, characterized in that: The raw materials of the phenolic resin precursor solution include the following components: resorcinol, formaldehyde and ammonia water.

7. The method according to claim 5, characterized in that: The carbonizing of the wood also includes the following steps: cutting the wood into wood chips perpendicular to its growth direction, placing the wood chips in a protective atmosphere, and heating the chips at 800-850° C. to obtain carbonized wood with orderly arranged vertical pores.

8. A method for degrading tetracycline in a solution using a floating cathode electro-Fenton system as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: A solution containing tetracycline and a catalyst are added to the floating cathode electro-Fenton system to obtain a mixed solution, which is electrolyzed to degrade the tetracycline in the solution.

9. The method according to claim 8, characterized in that: The catalyst comprises Fe 2+ Compounds, of which Fe 2+ The concentration in the mixed solution is 0.2-0.4 mol / L.

10. The method according to claim 8, characterized in that: The pH value of the mixed solution is 1-5.

Citation Information

Patent Citations

  • Floating type gas diffusion electrode for gas consumption reaction and preparation of floating type gas diffusion electrode

    CN107317040A

  • Floating type double-oxygen-source gas diffusion electrode device and application

    CN112408554A

  • Bipolar synergistic transmission type electro-Fenton device and method for degrading florfenicol

    CN113880196A

  • Floating type natural air diffusion electro-Fenton electrode and method for treating refractory sewage

    CN116768328A

  • Electrocatalytic fenton oxidation-electrochemical oxidation coupling process and apparatus for efficient treatment of chemical wastewater

    US20220048801A1